GRANT SULTAN IN ROYAL DELI AT 1890-1942 - Muhammad Nur; Suprayitno .; Edy Ikhsan (Jurnal Education and Development, 2021)
This research is entitled “Grant Sutan Di kerajaan Deli 1890-1942”. In the discussion, there are two main points in this problem, namely explaining the background of the policy and its implementation in the field. Previously, to see the changes that have occurred and the supporting factors that support the general picture of Gemeente Medan. From this investigation, it can be seen that the factors behind the existence of the colonial Sutan policy regarding burial land rights in Gemeente Medan were the development of the Gemeente Medan government, the management of infrastructure in Gemeente Medan, and the regulation and prevention of inter-ethnic conflicts. In the part that is the core of this research problem regarding the implementation of the colonial government policy regarding the Grant land in Gemeente Medan in 1890-1942. In this section the regulations regarding statutory regulations, the management body for the distribution of land for grants, and government regulations that apply to government policies regarding the distribution of grants. The formation of Gemeente Medan was based on a decree contained in Staatsblad 1909 No. 180, one of the contents is a matter of land arrangement. Arrangements are arranged based on grouping carried out based on existing groups. The policy in effect has a practical objective for the city government, namely to generate tax money and income for the financial treasury of Gemeente Medan. However, burial ground arrangements also have a purpose in urban and environmental planning. Apart from that, laws and regulations and policies for European groups, according to the government, have contributed greatly to the development of Gemeente Medan. In general, the regulations regarding the division of Grant's land in Gemeente Medan were divided into two, namely the land for the Earthutera and the Eroah people which was managed by the Gemeente government and the Sultanate. This management sometimes results in overlapping policies between the two governments. Gemeente government regulations regarding the agreement for all residents of the Gubernemen even though they live in the sultanate. Meanwhile, the sultanate had the authority to regulate burial land assistance under their jurisdiction, so that the Gemeente government did not have the authority to regulate the area of ​​the sultanate.